2020
DOI: 10.3390/ijms21155476
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model for Bax∆2-Mediated Activation of Caspase 8-Dependent Apoptosis

Abstract: Bax∆2 is a pro-apoptotic anti-tumor protein in the Bax family. While most of the Bax family causes cell death by targeting mitochondria, Bax∆2 forms cytosolic aggregates and activates caspase 8-dependent cell death. We previously showed that the Bax∆2 helix α9 is critical for caspase 8 recruitment. However, the interaction between these two proteins at the structural level is unknown. In this in silico study, we performed molecular dynamics (MD) simulations and protein–protein docking on Bax∆2 variants. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The Baxα C-terminal tail contains a transmembrane domain for anchoring on mitochondria. When Bax proteins fail to target mitochondria and form aggregates, these tails are accessible for binding to the caspase 8 N-terminal death effector domain in cancer cells [ 21 ]. We demonstrated that the α9 helical structure rather than the primary sequence was critical for Bax∆2 binding to caspase 8 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Baxα C-terminal tail contains a transmembrane domain for anchoring on mitochondria. When Bax proteins fail to target mitochondria and form aggregates, these tails are accessible for binding to the caspase 8 N-terminal death effector domain in cancer cells [ 21 ]. We demonstrated that the α9 helical structure rather than the primary sequence was critical for Bax∆2 binding to caspase 8 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Can Bax∆2 still cause cell death if it cannot target mitochondria? We have uncovered the mechanism of Bax∆2-mediated cell death using both wet and dry lab approaches [ 19 , 20 , 21 ]. Although Bax∆2 did not target mitochondria due to the lack of exon 2 encoding helix α1, it contains an intact core region capable of oligomerization [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the parental Baxα, Bax∆2 has a stronger pro-death potency [8]. Unlike most members of the pro-apoptotic Bax family which trigger apoptosis through the mitochondrial pathway, Bax∆2 proteins are unable to target mitochondria, instead they accumulate in the cytosol as protein aggregates, activating caspase 8dependent apoptosis [9]- [11]. Expression of Bax∆2 protein in human tissues has been well characterized by immunohistochemistry with anti-Bax∆2 antibody [12], [13].…”
Section: Introductionmentioning
confidence: 99%